High‐Purity Prostate Circulating Tumor Cell Isolation by a Polymer Nanofiber‐Embedded Microchip for Whole Exome Sequencing. (26th March 2013) - Zhao, Libo; Lu, Yi‐Tsung; Li, Fuqiang; Wu, Kui; Hou, Shuang; Yu, Juehua; Shen, Qinglin; Wu, Dongxia; Song, Min; OuYang, Wei‐Han; Luo, Zheng; Lee, Tom; et al.
<x xml:space="preserve">Abstract</x> Handpick single cancer cells: A modified NanoVelcro Chip is coupled with ArcturusXT laser capture microdissection (LCM) technology to enable the detection and isolation of single circulating tumor cells (CTCs) from patients with prostate cancer (PC). This new approach paves the way for conducting next‐generation sequencing (NGS) on single CTCs. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>